Linux in a nutshell : a desktop quick reference - Hekman, Jessica Perry (O'Reilly, 1997)
"Linux in a Nutshell covers the core commands available on common Linux distributions. This isn't a scaled-down quick reference of common commands, but a complete reference containing all user, programming, administration, and networking commands." "Many UNIX users who have GNU versions of standard UNIX tools will also enjoy this book because it documents a wide range of GNU tools." "This book includes all the essential commands you need to run your system and all the commands that historically have been included on UNIX systems. Specialized packages included in many popular distributions of Linux are not covered."--Jacket.